2009
DOI: 10.1158/0008-5472.can-08-1996
|View full text |Cite|
|
Sign up to set email alerts
|

LY303511 Enhances TRAIL Sensitivity of SHEP-1 Neuroblastoma Cells via Hydrogen Peroxide–Mediated Mitogen-Activated Protein Kinase Activation and Up-regulation of Death Receptors

Abstract: We recently reported that LY294002 (LY29) and LY303511 (LY30) sensitized tumor cells to drug-induced apoptosis independent of the phosphoinositide 3-kinase/Akt pathway. Here, we investigated the mechanism of LY30-induced sensitization of human neuroblastoma cells to TRAILmediated apoptosis. We provide evidence that LY30-induced increase in intracellular H 2 O 2 up-regulates the expression of TRAIL receptors (DR4 and DR5) in SHEP-1 cells by activating mitogen-activated protein kinases, resulting in a significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 46 publications
6
76
1
Order By: Relevance
“…It has already been documented that ROS can activate ERK1/2, which leads to the induction of DR5 and DR4. In addition, LY303511 has been shown to augment TRAIL-induced apoptosis through ERK-mediated upregulation of DR5 and DR4 (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been documented that ROS can activate ERK1/2, which leads to the induction of DR5 and DR4. In addition, LY303511 has been shown to augment TRAIL-induced apoptosis through ERK-mediated upregulation of DR5 and DR4 (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mitogen-activated protein kinases (MAPK), ERK1/2, can regulate the upregulation of DRs by bisindolylmaleimide and LY303511 (38,39). We tested whether γ-T3 mediates its effects through a similar mechanism.…”
Section: γ-T3 Upregulates Drs Through Erkmentioning
confidence: 99%
“…Similarly, high levels of intracellular H 2 O 2 (>1 μM) depletes cellular thioredoxin pool and increases oxidation of glutathione (GSH) and oxidative inactivation of general cellular thiolate-dependent enzymes [33]. Also, H 2 O 2 inhibits thiolate dependent enzymes by oxidation of their active-site thiolate moieties [34]. Similarly, SOD activity was inhibited by H 2 O 2 associated with the reduction of the active site of SOD (Cu 2+ to Cu+), and/or the structural alteration of SOD that restricts access to Cu 2+ [35,36].…”
Section: Cytoprotection and Antioxidant Activitymentioning
confidence: 99%
“…Because ROS are implicated in the activation of MAPK (38,44) and because azadirone induced ROS, we investigated whether azadirone-induced activation of MAPK is ROS-dependent. Cells were treated with NAC for 1 h before treatment with azadirone for 0.5-8 h. The treatment of cells with NAC abolished azadirone-induced activation of ERK (Fig.…”
Section: Activation Of Mapk Is Required For Up-regulation Of Dr5 and mentioning
confidence: 99%